Recombinant antigens expressed in Pichia pastoris for the diagnosis of sleeping sickness caused by Trypanosoma brucei gambiense. - Stijn Rogé; Liesbeth Van Nieuwenhove; Magali Meul; Annick Heykers; Annette Brouwer de Koning; Nicolas Bebronne; Yves Guisez; Philippe Büscher (Public Library of Science (PLoS), 2014)
Screening tests for gambiense sleeping sickness, such as the CATT/T. b. gambiense and a recently developed lateral flow tests, are hitherto based on native variant surface glycoproteins (VSGs), namely LiTat 1.3 and LiTat 1.5, purified from highly virulent trypanosome strains grown in rodents.We have expressed SUMO (small ubiquitin-like modifier) fusion proteins of the immunogenic N-terminal part of these antigens in the yeast Pichia pastoris. The secreted recombinant proteins were affinity purified with yields up to 10 mg per liter cell culture.The diagnostic potential of each separate antigen and a mixture of both antigens was confirmed in ELISA on sera from 88 HAT patients and 74 endemic non-HAT controls. Replacement of native antigens in the screening tests for sleeping sickness by recombinant proteins will eliminate both the infection risk for the laboratory staff during antigen production and the need for laboratory animals. Upscaling production of recombinant antigens, e.g. in biofermentors, is straightforward thus leading to improved standardisation of antigen production and reduced production costs, which on their turn will increase the availability and affordability of the diagnostic tests needed for the elimination of gambiense HAT.